Rural EFL Teachers’ Emotions and Agency in Online Language Teaching: I Will Survive - Dini Rosita Sari (Vision: Journal for Language and Foreign Language Learning, 2021)
This article explores rural English as a Foreign Language (EFL) teachers’ emotions and agency in online language teaching. Based on Hargreaves’s emotional geography framework, teachers’ emotions and teacher agency are both captured through teachers’ narration about their feelings, salient challenges that they encountered, and their coping strategies. Research data were collected using semi-structured interviews with two English teachers working in rural upper secondary schools in Nunukan, Indonesia. The collected data were analyzed with an inductive approach. The findings portray how rural EFL teachers experience various emotions which are mainly caused by physical and sociocultural distance, how agency helps these teachers with abilities to reflect on their feelings and to take crucial actions, and to what extend the need for immediate professional development programs to develop online teaching skills is.